Chlorhexidine versus saline in reducing the risk of catheter associated urinary tract infection: A cost-effectiveness analysis. (September 2019) - Mitchell, Brett G.; Fasugba, Oyebola; Cheng, Allen C; Gregory, Victoria; Koerner, Jane; Collignon, Peter; Gardner, Anne; Graves, Nicholas
Abstract: Background: Catheter associated urinary tract infections are one of the most common infections acquired in hospital. A recent randomised control study demonstrated the benefit of using chlorhexidine (0.1%) for meatal cleaning prior to urinary catheter insertion, by reducing both catheter associated asymptomatic bacteriuria and infection. These findings raise the important question of whether a decision to switch from saline to chlorhexidine was likely to be cost-effective. The aim of this paper was to evaluate the cost-effectiveness of adopting routine use of chlorhexidine for meatal cleaning prior to urinary catheter insertion Methods: The outcomes of this cost-effectiveness study are changes to health service costs in AUD and changes to quality adjusted life years from a decision to adopt 0.1% chlorhexidine for meatal cleaning prior to urinary catheter insertion as compared to saline. Effectiveness outcomes for this study were taken from a 32 week stepped wedge randomised controlled study conducted in three Australian hospitals. Results: The changes in health costs from switching from saline to 0.1% chlorhexidine per 100, 000 catheterisations would save hospitals AUD387, 909 per 100, 000 catherisations, prevent 70 cases of catheter associated urinary tract infections, release 282 bed days and provide a small improvement in health benefits of 1.43 quality adjusted life years. Using a maximum willingness to pay for a marginal quality adjusted life year threshold of AUD28, 000 per 100, 000 catherisations, suggests that adopting chlorhexidine would be cost effective and potentially cost-saving. Conclusion: The findings from our work provide evidence to health system administrators and those responsible for drafting catheter associated urinary tract infections prevention guidelines that investing in switching from saline to chlorhexidine is not only clinically effective but also a sensible decision in the context of allocating finite healthcare resources.